The Study of African Leave (Vernonia amygdalina) in for Improving the Quality of Local Duck Meats of West Sumatera - Zasmeli Suhaemi; Zulkarnaini Zulkarnaini; Afrijon Afrijon; PN Jefri (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
This research purpose to observe the response of local duck, especially male duck that given African Leaf Flour (ALF) in the diet, toward body weight and blood cholesterol content. The treatment for this research will be given by differentiate the ALF level in five levels (0%, 0.5%, 1.0%, 1.5%, and 2.0%) with four times replication. This research used Completely Randomized Design. This treatment is obsessed to 80 male ducks which are rearing from the age of 4 until 10 weeks. The result showed that the increasing of ALF level in diets, will highly significant increase the body weight growth (BWG) of duck, as the increasing value of BWG is 23.59% (P<0,01), and its similarly with the Feed Conversion Ratio (FCR). The blood cholesterol content is decreasing to 7.41% for 1.5% the ALF level given (P<0,01), while the content of cholesterol-HDL and LDL has not significantly (P>0,05). However, the content of cholesterol-HDL in blood tend to increase along with the increasing of the ALF level given. Utilization of ALF level until 2.0% could increase the quality of local duck meat, because its produce higher meat production and improve the content of cholesterol for creating healthy animal food sources.